Accurate Correlation Potentials from the Self-Consistent Random Phase Approximation - Trushin, Egor; Fauser, Steffen; Mölkner, Andreas; Erhard, Jannis; Görling, Andreas (Physical Review Letters, 2025)
Density-functional theory (DFT) within the Kohn-Sham (KS) formalism is the most widely used approach to treat electronic structures of molecules and solids in physics, chemistry, and materials science, and the development of more accurate functionals for the KS exchange and correlation energy has been a major research focus for decades. The corresponding exchange and correlation potentials, on the other hand, have attracted little attention. Those cases for which reference potentials are available showed that in particular correlation potentials from common approximate density functionals are of poor quality and sometimes have little in common with the exact potentials. This hampers the further development of KS-DFT. Here, we show that highly accurate correlation potentials can be obtained within the random phase approximation (RPA). In conjunction with the exact exchange potential, which, like the RPA correlation potential, is accessible within the optimized effective potential method, highly accurate exchange-correlation potentials are available and provide a basis for the further development of DFT. We present a numerically stable approach for efficiently carrying out self-consistent RPA calculations and combine it with a KS inversion method to obtain reference correlation potentials from highly accurate electron densities from coupled cluster calculations. Accurate exchange-correlation potentials have to yield KS eigenvalues for the highest occupied molecular orbital that are close to the negative of the ionization potential. This is indeed the case, the RPA highest occupied molecular orbital eigenvalues yield ionization potentials that can compete with GW ionization potentials.
CRIS-Team Scopus Importer:2025-02-28

Phenylphosphonic Acid on Rutile TiO2(110): Using Theoretically Predicted O 1s Spectra to Identify the Adsorption Binding Modes - Wolfram, Alexander; Muth, Maximilian; Köbl, Julia; Mölkner, Andreas; Mehl, Sascha; Tsud, Nataliya; Steinrück, Hans-Peter; Meyer, Bernd; Lytken, Ole (Journal of Physical Chemistry C, 2024)
We have studied the adsorption of phenylphosphonic acid on rutile TiO2(110)-(1 × 1) using high-resolution synchrotron-radiation photoelectron spectroscopy and near-edge X-ray absorption fine-structure spectroscopy (NEXAFS). Upon adsorption at room temperature, we observe a complex O 1s spectrum, a single P 2p multiplet and the disappearance of small polarons in the Ti 2p and valence-band regions. Upon heating to 450-500 K, the O 1s spectrum changes, an additional P 2p species appears, the polaron signals reappear even stronger and NEXAFS indicates a more flat-lying molecule. Using density functional theory (DFT), we have determined the most stable adsorption configurations on the surface. For these configurations, we have calculated the O 1s and P 2p binding-energy positions of all oxygen and phosphorus atoms, including the first three trilayers of the TiO2(110) substrate. In addition, we have used the orientations of the phenyl rings from the DFT structures to calculate the expected polar and azimuthal angular dependencies in carbon K-edge NEXAFS. This allows us to compare our calculated adsorption configurations with the experimental observations. Below 450 K, we find a singly deprotonated bidentate species to be in perfect agreement with the experimental data. Above 500 K, the desorption of water creates oxygen vacancies, and we find a mixed bidentate and rotated-tridentate adsorption structure to be in good agreement with the experimental observations.
CRIS-Team Scopus Importer:2024-07-26